Bridge engineering : classifications, design loading, and analysis methods - Lin, Weiwei (Butterworth-Heinemann, 2017)
This book explores the theory and practice of bridge engineering, design and planning, materials and construction, loads and load distribution, and deck systems. It covers such applications as reinforced and prestressed concrete bridges, steel bridges, truss bridges, arch bridges, cable bridges, suspension bridges, bridge piers, and bridge substructures, as well as issues commonly found in inspection, monitoring, repair, strengthening, and replacement of bridge structures.